Usefulness of detection of complement activation products in evaluating SLE activity - Nagy, György; Brózik, M.; Varga, L.; Füst, G.; Kirschfink, Michael; Kiss, E.; Gergely, P. (Lupus, 2000)
Complement activation products, such as C1rs-C1inh, specific for the activation of the classical pathway, C3b(Bb)P, specific for the activation of the alternative pathway and SC5b-9, specific for common terminal pathway of the complement cascade, were measured in healthy donors and in patients with clinically active and inactive systemic lupus erythematosus (SLE). Plasma levels of C3b(Bb)P and SC5b-9 were moderately, those of C1rs-C1inhibitor (C1rs-C1inh) were markedly elevated in patients with clinically inactive SLE, compared with healthy controls. The difference between active and inactive stages of the disease was best reflected by C3b(Bb)P plasma concentration (P<0.001), which also showed the highest correlation with the SLEDAI (Rs=0.41 P<0.001) and which was the most useful in distinguishing active and inactive sample pairs as well. The difference between SC5b-9 levels in the active and inactive stages was also significant (P=0.007), while that of C1rs-C1inh did not differ significantly (P=0.136). The correlation of the SLEDAI with SC5b-9 was 0.3 (P=0.015), while with C1rs-C1inh it was 0.21 (P=0. 089). These findings suggest that the measurement of complement activation products, especially that of the alternative pathway, are sensitive markers of the activity of SLE and can be used for clinical purposes.